Complete Genome Sequences of Two Novel KPC-2-Producing IncU Multidrug-Resistant Plasmids From International High-Risk Clones of Escherichia coli in China - Wu, Wenhao; Lu, Lingling; Fan, Wenjia; Chen, Chun; Jin, Dazhi; Pan, Hongying; Li, Xi (Frontiers in Microbiology, 2021)
The rapidly increasing prevalence of Klebsiella pneumoniae carbapenemase 2 (KPC-2)-producing bacteria has become a serious challenge to public health. Currently, the blaKPC-2 gene is mainly disseminated through plasmids of different sizes and replicon types. However, the plasmids carrying the blaKPC-2 gene have not been fully characterized. In this study, we report the complete genome sequences of two novel blaKPC-2-harboring incompatibility group U (IncU) plasmids, pEC2341-KPC and pEC2547-KPC, from international high-risk clones of Escherichia coli isolated from Zhejiang, China. Two KPC-2-producing E. coli isolates (EC2341 and EC2547) were collected from clinical samples. Whole-genome sequencing (WGS) analysis indicated that EC2341 and EC2547 belonged to the ST410 and ST131 clones, respectively. S1-nuclease pulsed-field gel electrophoresis (S1-PFGE), Southern blot and conjugation experiments confirmed the presence of the blaKPC-2 gene on the pEC2341-KPC plasmid and that this was a conjugative plasmid, while the blaKPC-2 gene on the pEC2547-KPC plasmid was a nonconjugative plasmid. In addition, plasmid analysis further revealed that the two blaKPC-2-harboring plasmids have a close evolutionary relationship. To the best of our knowledge, this is the first report of E. coli strains carrying the blaKPC-2 gene on IncU plasmids. The emergence of the IncU-type blaKPC-2-positive plasmid highlights further dissemination of blaKPC-2 in Enterobacteriaceae. Therefore, effective measures should be taken immediately to prevent the spread of these blaKPC-2-positive plasmids.